Impact of illegal mining activities on forest ecosystem services: local communities' attitudes and willingness to participate in restoration activities in Ghana. Issue 10 (October 2019) - Obeng, Elizabeth Asantewaa; Oduro, Kwame Antwi; Obiri, Beatrice Darko; Abukari, Haruna; Guuroh, Reginald Tang; Djagbletey, Gloria Djaney; Appiah-Korang, Joseph; Appiah, Mark
Abstract: Understanding local communities' willingness to participate in environmental restoration activities can help assess the level of volunteerism that can be expected for restoration projects. This study ascertained local communities' perception of the importance of non-market ecosystem services, the impact of illegal mining on ecosystem services, and their likeliness to participate in restoration of degraded lands resulting from illegal mining. Fifty respondents each were purposefully selected from three mining communities (Ntakam, Asawinso No.1 and Nkatieso) in a survey. Analysis of variance (ANOVA) tests results indicated there were no difference in views of respondents regarding the importance of forest for various non-market services. Illegal mining activities were identified as the cause of environmental problems such as water pollution, deforestation, poor soil fertility and limited access to land for agriculture productivity. Majority of respondents across the three communities indicated that forest is very important for non-market environmental services. Logistic regression results indicated that factors that affect likeliness to participate in restoration financing included income, embracing non-market ecosystem services as important, confidence in PES schemes and positive value motivation for restoration (altruistic, use and bequest values). Abstract : Agricultural economics; Agricultural policy; Agronomy; Agroforestry; Ecology; Environmental analysis; Environmental assessment; Environmental economics; Environmental management; Economics; Illegal mining; Ecosystem services; Degraded mined sites; Community participation; Restoration.